Stochastic evolution mechanism in random thermoelastic vibration captured using the explicit time-domain method. (1st September 2021) - Li, Yingxiong; Su, Cheng
Highlights: A novel approach is developed for stochastic analysis of fully coupled thermoelastic problems. The physical mechanism and the stochastic evolution mechanism involved are treated separately with the explicit time-domain method. The explicit time-domain expressions of system responses are constructed via deterministic impulse response analyses. Dimension-reduced stochastic analysis can be conducted focusing on critical responses with high computational efficiency. Graphical abstract: Abstract: Thermoelastic vibration under random excitations is a frequently encountered challenge in modern engineering. The stochastic evolution mechanism involved needs to be quantified using novel and efficient procedures. This paper extends the explicit time-domain method (ETDM), which is a powerful tool originally developed for structural random vibration, to the stochastic analysis of coupled thermoelastic problems. To efficiently solve the stochastic evolution equations, the explicit time-domain expressions of critical responses are first constructed via a deterministic impulse response analysis. Then, using the explicit expressions the statistics of the random system responses can be efficiently computed. Thus, in ETDM the physical mechanism and the stochastic evolution mechanism are treated separately. This feature makes the method particularly suitable for stochastic multiphysics problems like thermoelastic vibration, where the physical mechanisms involved are relatively complex. Its capability is shown by considering coupled displacement and temperature field in large scale problems with non-stationary random inputs. Numerical examples are presented to demonstrate the efficiency and accuracy of the method with emphasis on structural reliability assessments.